Some considerations on the prevention of child sexual abuse - Deza Villanueva, Sabina (2005)
Child sexual abuse is considered one of the child maltreatment ways. The basic criteria for this typifying are also established. According to the Finkelhor and Krugman model, the conditions for its occurrence are explained. Indicators for assessing, protecting or compensating and for risk or potentiating factors are proposed by the Program of Sensibilization and Prevention of Child Sexual Abuse (Save the Children), Finally, the measures to prevent protective factors for sexual abuse strengthening in children and their families are established.